Uji Identifikasi Bakteri Coliform Pada Tahu Putih Oleh Penjual Di Pasar Sedondong Batang - Dwi Hariyanti; Nila Oktaviani (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Food is used as a basic necessity for human life. Food can increase the growth and development of the body and can repair damaged body tissue. Food and drinks that will be distributed and consumend by the public must comply with the quality standards that have been set. One of the microorganisms most often found in food and drinks in Coliform bacteria. Coliforms are a group of bacteria that can be used as an indicator of the presence of pathogens that are detrimental or not beneficial for water, food, milk and dairy products. The aim of this research was to determine whether or not Coliform bacteria were present in white tofu sold at the Sedondong Batang market. The type of research used is descriptive research. This research was carried out on November 28, 2023. Sample examination was carried out at the Pekalongan Regency KESDA Laboratory. The samples used in this research were white tofu sold at the Sedondong Batang market, totaling 4 samples. In this research, the sampling technique was purposive sampling. The method used the MPN method, MPN is a method used to count Coliforms in water using in-tube fermentation testing. This method requires two tests, namely a predictor test and a reinforcement test.